Strategies for Implementing Religious Moderation in the Social Life of the Bengabing Village Community - Afifah Hanum Lubis; Oktrigana Wirian (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze strategies for implementing religious moderation in the social life of the Bengabing Village community. Religious moderation is an essential concept in fostering social harmony, preventing conflict, and building an inclusive and tolerant society. This research employs a qualitative approach using field studies through in-depth interviews, observations, and documentation. The findings reveal that the main strategies for implementing religious moderation include strengthening the role of religious leaders, promoting collaboration between educational institutions and village authorities, and internalizing moderation values through religious and community-based activities. Additionally, local wisdom and cooperative cultural practices significantly contribute to creating a harmonious social environment. The study recommends developing sustainable religious moderation programs to maintain social stability and enhance intercommunity tolerance.